Mismatch between health-care professionals' and patients' views on a diabetes patient decision aid: a qualitative study - Lee, Ping Yein; Khoo, Ee Ming; Low, Wah Yun; Lee, Yew Kong; Abdullah, Khatijah Lim; Azmi, Syahidatul Akmal; Ng, Chirk Jenn (John Wiley & Sons, 2016)
Background: Malaysia is an Asian country with population of diverse culture and health perceptions. Patient decision aid (PDA) is a new tool in Malaysia. Patients' and health-care professionals' (HCPs) expectation of a PDA is unknown. Aim: We aimed to explore patients' and health-care professionals'(HCPs) views on the information needed in a patient decision aid (PDA) on insulin initiation developed for patients with type 2 diabetes mellitus (T2DM). Design: We used a qualitative design and thematic approach. Setting: Three main primary health-care settings in Malaysia: public university-based primary care clinics, public health-care clinics and private general practices. Method: We conducted focus groups and one-to-one interviews with a purposive sample of health professionals and patients with type 2 diabetes. Results: We interviewed 18 patients and 13 HCPs. Patients viewed the content of the PDA as simple and clear. However, HCPs felt the PDA might be difficult for patients with low literacy to understand. HCPs thought the PDA was too lengthy. Nevertheless, patients would prefer more information. HCPs tended to focus on benefits of insulin, while patients wanted to know the impact of insulin on their quality of life and practical issues regarding insulin and its side-effects. Patients preferred numbers to weigh the risks and benefits of treatment options. HCPs' views that presenting numbers in a PDA would be too complex for patients to understand. Conclusion: It is important to consider including issues related to psycho-social impact of treatment to patients when developing a patient decision aid.